RANCANG BANGUN DAN UJI COBATUNGKU KRUSIBEL DARI TABUNG GAS BEKAS DENGAN MENGGUNAKAN SUMBER PANAS GAS LPG - Aminur Aminur; Kadir Kadir; Muhammad Hasbi; Sudarsono Sudarsono; Yuspian Gunawan; La Hasanudin; Raden Rinova Sisworo; Al Ichlas Imran (Jurnal Teknologi Terapan, 2020)
The availability of crucible furnaces is still limited, so the price in the market is relatively expensive, even though this tool is very important, especially in educational institutions as media for the practice of metal casting. The purpose of this study is to design, build and test the work of a crucible furnace that utilizes used cylinders by using LPG gas heat sources. The design of the furnace uses the autodesk inventor application while the manufacture uses machine tools. Technical data from this crucible furnace is that the body is made from used gas cylinders with an outer diameter of 280 mm, an inner diameter of 140 mm and a height of 490 mm. In the combustion chamber installed a 25.4 mm diameter gas pipeline with a length of 370.5 mm and an air channel diameter of 50.8 mm with a length of 367 mm. Kowi is made of steel with a 110 mm dimension and a height of 280 mm. The results of trials with aluminum smelting show that the crucible furnace is capable of melting 5 kg aluminum for 60 minutes with fuel consumption of 3 kg gas. The maximum temperature that can be reached 1367 oC for 15 minutes by a crucible furnace.Keywords: design, manufacture, furnace trials